Role Transformation of National Sharia Board-Indonesian Ulama Council (DSN-MUI) in the Dynamics of Fatwa Determination in the Modern Era - Dyah Ayu Marrantika; Selvionita Selvionita; Rizki Ramadhan; Zaitun Qamariah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The role transformation of the National Sharia Board Dewan Syariah Nasional (DSN); one of the organizational structures in Indonesian Ulama Council Majelis Ulama Indonesia (MUI) in the dynamics of fatwa determination in the modern era is an important topic to be studied in the context of rapid social, economic, and technological change. This article aims to analyze how DSN-MUI adapts to the challenges of modern times and develops a methodology for setting fatwas that is relevant and responsive to the needs of contemporary society. Through a comprehensive literature review, this article highlights the evolution of the DSN's function from the establishment of conventional fatwas towards a more dynamic and inclusive approach, including in the field of sharia finance, halal products, and other social problems. This transformation reflects DSN-MUI's efforts to remain relevant and provide accurate and applicable guidance for Muslims in Indonesia in facing modern issues.